2019
DOI: 10.1007/s12192-019-00977-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of ginkgolides and bilobalide against cerebral ischemia injury by activating the Akt/Nrf2 pathway in vitro and in vivo

Abstract: Ginkgolide terpenoid lactones, including ginkgolides and bilobalide, are two crucial bioactive constituents of extract of Ginkgo biloba (EGb) which was used in the treatment of cardiovascular and cerebrovascular diseases. The aims of this study were to investigate the antioxidant effects and mechanism of ginkgolides (ginkgolide A (GA), ginkgolide B (GB), ginkgolide K (GK)) and bilobalide (BB) against oxidative stress induced by transient focal cerebral ischemia. In vitro, SH-SY5Y cells were exposed to oxygen-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 54 publications
0
109
0
Order By: Relevance
“…The present study was undertaken to determine the roles of APE1 in the protective effects of curcumin against cerebral I/R injury, as well as to identify the molecular mechanisms through which curcumin affects SH-SY5Y neuronal cells subjected to oxygen-glucose deprivation/reperfusion (OGd/R), a commonly used in vitro model of cerebral I/R injury (24,25). It was observed that curcumin protected the SY-SH5Y cells against OGd/R injury by upregulating APE1 expression, which is associated with the regulation of the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling pathway.…”
Section: Curcumin Exerts Protective Effects Against Hypoxia-reoxygenamentioning
confidence: 99%
“…The present study was undertaken to determine the roles of APE1 in the protective effects of curcumin against cerebral I/R injury, as well as to identify the molecular mechanisms through which curcumin affects SH-SY5Y neuronal cells subjected to oxygen-glucose deprivation/reperfusion (OGd/R), a commonly used in vitro model of cerebral I/R injury (24,25). It was observed that curcumin protected the SY-SH5Y cells against OGd/R injury by upregulating APE1 expression, which is associated with the regulation of the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling pathway.…”
Section: Curcumin Exerts Protective Effects Against Hypoxia-reoxygenamentioning
confidence: 99%
“…Dorema aucheri extract was reported to possess neuroprotective effects in ischemia-reperfusion injury in rats [11]. Ginkgolides and bilobalide were reported to have antioxidant effects in cerebral ischemia injury via activation of the Akt/Nrf2 pathway [12]. Methyl protodioscin was found to show protective effects in ischemia/reperfusion injury in rats [13].…”
Section: Introductionmentioning
confidence: 99%
“…As a vital component in G biloba extractive, BIL can decrease blood pressure, reduce the heart rate, restrain ischemia‐reperfusion damage, and platelet aggregation and so on . Liu et al found that BIL had functions with regard to cerebral ischemic damage. Sui et al found that BIL can protect cuprizone‐induced demyelination.…”
Section: Discussionmentioning
confidence: 99%